Kratom use, psychiatric comorbidity and the psychosocial correlates among FELDA settlers in northern Peninsular Malaysia / Al-Zilal Abdul Wahid - Al-Zilal, Abdul Wahid (2018)
Kratom use, psychiatric comorbidity and the psychosocial correlates among FELDA settlers in Northern Peninsular Malaysia Introduction: Kratom (Mitragyna Speciosa, Korth) is an indigenous plant of South East Asia, particularly in Malaysia, Thailand, and Indonesia. For centuries people use Kratom as a traditional remedy to treat various ailments. Its inclusion into the New Psychoactive Substance (NPS) and extensive availability have brought about concerns regarding its current use, and potential harm. Despite the rising concerns, the prevalence of its use among rural settlers, its sociodemographic factors as well as the impact on mental illness of regular-users and quality of life is scarce. Objectives: The study aims at finding the prevalence of Kratom use among the rural settlers in a Felda settlement, located in the northern region of Malaysia. Its associating factors, as well as any psychiatric co-morbidities, is examined to ascertain the effects of Kratom use among the respondents. Method: The study recruited participants on a voluntary basis. The study chose the largest Felda settlement in Perlis. Its residents all originate from Perlis and have stayed at the site for generations. The study obtained the sociodemographic data, and trained individuals assessed all the respondents using the MINI, ASSIST-M, WHOQoL-Bref questionnaires. viii Results: The study recruited a total sample of 144 participants. The Kratom users were determine using the MINI, the ASSIST-M and the WHOQoL-BREF-Malay Version questionaire. The prevalence of Kratom use was 24.3% (n=35) among the participants. The univariate analysis found statistically significant association (p<0.01) between the Kratom user and age, gender, marital status, education level, employment status, general illness, history of illicit substance use, the presence of family members abusing illicit substance, smoking and opioid dependency. The multiple logistic regression analysis identified a significant association between Kratom users with history of drug, and tobacco use. The participants with moderate and high tobacco use and past and present other substance usage are likely to be a Kratom-user. In the assessment of their quality of life, Kratom-users reported feeling physically healthier than the non-users. However, though close to 70% are employed, their average income is less than two thousand ringgits per month. Moreover, among the Kratom-users, almost all are smokers, smoking an average of 20 sticks per day (IQR=10) and they started smoking at a mean age of 15.4 years (SD=3.35). Conclusion: The study found a high prevalence of Kratom-use among the rural settlers. The study identified a robust association of Kratom use with tobacco and opioid usage. The participants with moderate and high tobacco use plus past and present other substance use are likely to be a Kratom-user. The study concludes the severity of the problem is chronic and worrying. The report should serve as a precursor for further researches in this area as well as possible health policy-making.